Children and Youth With Asperger Syndrome : Strategies for Success in Inclusive Settings. - Smith Myles, Brenda (SAGE Publications, 2005)
How can you make the school year successful for your students with Asperger Syndrome? Asperger syndrome (AS) is a disorder in the autism spectrum, and students with AS suffer from similar, though milder, symptoms as students with autism. Classroom teachers who are responsible for planning for and teaching students with AS generally have not been provided the skills and knowledge to do so. Children and Youth With Asperger Syndrome provides important strategies in teaching children and youth diagnosed with AS. This essential resource for teachers and other educators presents research-based, ins.